A numerical investigation of the infrapatellar fat pad. (October 2020) - Fontanella, Chiara Giulia; Macchi, Veronica; Porzionato, Andrea; Arduino, Alessandro; Fotso Fongang, Joseph Vannel; De Caro, Raffaele; Natali, Arturo Nicola; Carniel, Emanuele Luigi
The infrapatellar fat pad is an adipose tissue in the knee that facilitates the distribution of synovial fluid and absorbs impulsive actions generated through the joint. The correlation between morphological configuration and mechanical properties is analyzed by a computational approach. The microscopic anatomy of the infrapatellar fat pad is studied aiming to measure the dimension of adipose lobules and the thickness of connective septa. Results from histomorphometric investigations show that the infrapatellar fat pad is an inhomogeneous tissue, constituted by large lobules in the superficial part and smaller lobules in the deepest one. Finite element models of the infrapatellar fat pad are developed. The first model considers the inhomogeneous conformation of the infrapatellar fat pad, composed of micro- and macro-chambers, while the second model considers a homogeneous distribution of adipose lobules with similar dimensions. Computational analyses are performed considering the static standing configuration and the passive flexion–extension movement. The computational results allow us to identify the different stress and strain fields within the tissue and to appreciate the variation of the mechanical performance of the overall system considering the distribution of adipose lobules. Results show that the distribution of adipose lobules in macro- and micro-chambers allows major deformation of the infrapatellar fat pad, decreasing the stress inside the tissues.